2000
DOI: 10.1136/jnnp.69.6.792
|View full text |Cite
|
Sign up to set email alerts
|

Brain tumours in Sweden 1996: care and costs

Abstract: Objectives-Brain tumours cause considerable concern due to a high mortality and there are increasing eVorts to provide adequate care, sometimes outside hospitals. Health care utilisation, direct costs of care, and the indirect social cost of morbidity and early mortality caused by brain tumours in Sweden in the year 1996 was analysed. Methods-Quantification of ambulatory care, care in hospital, long term and palliative/terminal care, drug consumption, temporary as well as long term morbidity, and mortality fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 36 publications
0
42
0
Order By: Relevance
“…For the year 1996, the AYPLL measure in Australia due to all brain and CNS tumors was 16.3 years, whereas in the UK, the data from 1990 to 1994 suggest an AYPLL measure of 20.1 years [5,16] . In a study in Sweden, the average loss of productive life years (up to 64 years) due to brain tumors in 1996 was 6.6 years [17] .…”
Section: Discussionmentioning
confidence: 99%
“…For the year 1996, the AYPLL measure in Australia due to all brain and CNS tumors was 16.3 years, whereas in the UK, the data from 1990 to 1994 suggest an AYPLL measure of 20.1 years [5,16] . In a study in Sweden, the average loss of productive life years (up to 64 years) due to brain tumors in 1996 was 6.6 years [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Brain tumors represent 1-2% of all newly diagnosed tumors and account for 2% of all cancer-related deaths. As with other neurologic diseases, brain tumors are particularly expensive to treat, with HAIs adding to costs 3,12 . In this study we evaluate the epidemiology, additional length of stay, incremental costs and patient outcomes due to hospital-acquired infections in brain tumor patients.…”
Section: Introductionmentioning
confidence: 99%
“…Costs of treatment for a brain tumour were extracted from Blomqvist 125 and are reported in Table 30. The authors reported direct and indirect costs of brain tumour.…”
mentioning
confidence: 99%